2022
DOI: 10.3390/ijms24010385
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression Patterns of Two Pheromone-Binding Proteins from the Diurnal Moth Phauda flammans (Walker) (Lepidoptera: Zygaenoidea: Phaudidae)

Abstract: Sex pheromone-binding proteins (PBPs) play an important role in sex pheromone recognition in Lepidoptera. However, the mechanisms of chemical communication mediating the response to sex pheromones remain unclear in the diurnal moths of the superfamily Zygaenoidea. In this study, Phauda flammans (Walker) (Lepidoptera: Zygaenoidea: Phaudidae) was used as a model insect to explore the molecular mechanism of sex pheromone perception in the superfamily Zygaenoidea. Two novel pheromone-binding proteins (PflaPBP1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In vitro and in vivo functional studies confirmed that PBP1 plays the major role and PBP2 and PBP3 are less important in female sex pheromone perception 9,14–17 . In addition to pheromone transportation, PBPs are also suggested to have roles in recognition among pheromone components, 18–21 and enhancement of the OR's sensitivity 22 …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In vitro and in vivo functional studies confirmed that PBP1 plays the major role and PBP2 and PBP3 are less important in female sex pheromone perception 9,14–17 . In addition to pheromone transportation, PBPs are also suggested to have roles in recognition among pheromone components, 18–21 and enhancement of the OR's sensitivity 22 …”
Section: Introductionmentioning
confidence: 91%
“…13 In vitro and in vivo functional studies confirmed that PBP1 plays the major role and PBP2 and PBP3 are less important in female sex pheromone perception. 9,[14][15][16][17] In addition to pheromone transportation, PBPs are also suggested to have roles in recognition among pheromone components, [18][19][20][21] and enhancement of the OR's sensitivity. 22 PRs refer to an OR subfamily that primarily function to perceive sex pheromone components, playing a central role in determining specificity of ORNs.…”
Section: Introductionmentioning
confidence: 99%